Cognitive behavioural treatment for problematic hoarding: A case study - James, Binnie (International Journal of Psychosocial Rehabilitation, 2025)
A fifty one year old man’s difficulties associated with hoarding are presented using a case study methodology. A psychological formulation and treatment plan is constructed following the work of a case study by Frost and Steketee, (1998). Despite some improvements in his functioning and clinical scores the overall reduction in clutter did not meet expectations. The focus of the discussion is the lack of published literature on hoarding behaviour, and the implications this has on interventions. Also highlighted are the issues associated with psychiatric diagnosis and the way in which this can influence decision making.